Forcible, Substance-facilitated, and Incapacitated Sexual Assault Among University Women: A Canadian Sample - Champion, Amanda (Journal of interpersonal violence, 2022)
This study examined the frequency of sexual assault experiences in a sample of university women to understand the conditions under which sexual assault occurs, and compare alcohol and drug consumption patterns on the likelihood of experiencing sexual victimization. While patterns of victimization have been examined in American contexts, research on contemporary Canadian contexts is scant at present. We found that roughly 58% of the 377 university women in our sample attending one of three large Western Canadian universities in British Columbia reported having been sexually assaulted. These women reported a total of 528 incidents of sexual assault, with 56% of these involving substance-related nonpenetrative sex acts; 312 incidents were substance-related and 216 involved forcible sexual assault. The likelihood of sexual assault victimization was the highest among participants who identified as a sexual minority, consumed marijuana, and reported greater severity of recent alcohol consumption. The present research aims to inform sexual assault prevention and education efforts to reduce occurrences of victimization.